Insights on the characteristics and therapeutic potential of mesenchymal stem cell-derived exosomes for mitigation of Alzheimer’s disease’s pathogenicity: a systematic review - Mohammed Yousuf Abdi, Sarah; Mustaffa Al-Bakri, Siti Sarah; Nordin, Norshariza (Springer, 2024)
Alzheimer’s disease (AD) remains a progressive neurodegenerative disease with no cure. Treatment of AD relies on administering drugs that only subside the symptoms. In recent studies, mesenchymal stem cell (MSC)-exosomes have been marked to possess therapeutic potential for treating AD. This study aims to systematically review and analyse findings that focus on the isolation, characterisation, and sources of MSC-derived exosomes used to unravel the therapeutic potential of these exosomes targeting AD using in vitro and in vivo models. It is hypothesised that MSC-exosomes exhibit high therapeutic potential for AD treatment by exerting various modes of action. PubMed, Scopus, and Medline were used to find relevant published works from January 2016 until December 2020, using assigned keywords including “Alzheimer’s disease”, “secretome”, and “exosomes”. Only research articles meeting the predefined inclusion/exclusion criteria were selected and analysed. The risk of bias was assessed using the Office of Health Assessment and Translation tool (OHAT). A total of 17 eligible in vivo and in vitro studies were included in this review. Bone marrow-derived stem cells (BMSCs) were the most used source for exosome isolation, even though studies on exosomes from adipose-derived stem cells (ADSCs) and human umbilical cord stem cells (HUCSCs) provide more information on the characteristics. When the risk of bias was assessed, the studies presented various levels of biases. Notably, the in vitro and in vivo studies revealed neuroprotective properties of MSC-exosomes through different modes of action to alleviate AD pathology. Our review discovered that most MSC exosomes could degrade Aβ plaques, enhance neurogenesis, extenuate neuroinflammatory response through microglial activation, regulate apoptosis and reduce oxidative stress. Delivery of exosomal micro-RNAs was also found to reduce neuroinflammation. Findings from this review provided convincing systematic evidence highlighting the therapeutic properties of MSC-derived exosomes as a prospective source for cell-free (acellular) therapy in treating AD.